Patients’ Satisfaction in Public and Private Primary Health Care: A Study in Karawang Regency, West Java, Indonesia - Meliannisa Afader; Putri Halleyana Adrikni Rahman; Deni Kurniadi Sunjaya (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Primary health care is the foundation of the Sustainable Development Goals (SDGs) to achieve Universal Health Coverage (UHC). Patient satisfaction with the health services acquired is one of the factors to achieve the UHC target. This study aimed to determine patients’ satisfaction in public and private primary health care centers.Methods: This quantitative analytic study with a cross-sectional method was conducted in five sub-districts of Karawang Regency based on community satisfaction surveys. The instrument used was a standard questionnaire with nine dimensions and filled with a survey approach by the respondents. Data was transformed from ordinal to numeric using Rach modelling. Then, numerical data were analysed with Chi Square Test in IBM SPSS Statistic 23 Version to determine differential between public and private groups. Results: In total, 193 respondents were included of whom 123 patients were from public health centers (Pusat Kesehatan Masyarakat, Puskesmas) and 70 from private primary care (clinic). Three dimensions had differences in satisfaction, including the requirements (p=0.001); systems, mechanisms, and procedures (p=0.001); and service time (p=0.001). The other six dimensions such as cost (p=0.534); product specification type of service (p=0.213); implementer competence (p=0.163); implementer behavior (p=0.000); handling of complaints, suggestions, and advances (p=0.448); and facilities infrastructure (p=0.063) were not proven to have differences in satisfaction. Overall, patients’ satisfaction level at Puskesmas (67.5%) was lower than at clinics (88.6%) (p=0.001).Conclusion: Patients’ satisfaction with the Puskesmas is lower than the clinic. Further study with a larger sample size and more complete dimension is needed.